2020
DOI: 10.1177/0021998320969794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infiltrated eutectic AlSi on the microstructure and properties of C/C composites

Abstract: Eutectic AlSi alloy was pressure infiltrated into a porous C/C skeleton to develop a low cost new C/C composite for application without extreme high temperature. C/C composite possessed a density of 1.7 g/cm3 was prepared for comparison. The effects of filling AlSi with and without Al-Ti-C grain refiner on the microstructure and properties of C/C composites were mainly studied. Result indicated that the introduced AlSi interpenetrated with C/C skeleton and made the composites compact. In comparison with C/C co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, the Si doping accelerated the selective oxidation of Al to generate an Al 2 O 3 protective layer. Unfortunately, during high-temperature corrosion exposure, the AlSi coatings suffered from significant elemental inter-diffusion [24][25][26][27][28][29][30]. According to the literature, the upward diffusion of Fe caused the creation of the (Fe 2 Al 5 + FeAl) alloy phase, which resulted in significant volume shrinkage and coating cracking.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Si doping accelerated the selective oxidation of Al to generate an Al 2 O 3 protective layer. Unfortunately, during high-temperature corrosion exposure, the AlSi coatings suffered from significant elemental inter-diffusion [24][25][26][27][28][29][30]. According to the literature, the upward diffusion of Fe caused the creation of the (Fe 2 Al 5 + FeAl) alloy phase, which resulted in significant volume shrinkage and coating cracking.…”
Section: Introductionmentioning
confidence: 99%
“…All the works indicated that the composites are promising materials for industrialization. In our recent study of C/C-AlSi, 22 the composites were prepared through pressure infiltration of eutectic AlSi into a fiber fabric based porous C/C skeleton in air, and the effect of grain refinement on the microstructure and property was discussed. To achieve a better and deeper infiltration, the C/C skeleton should be preheated to above 400 C which would result in oxidation of carbon and fast decreased strength of the C/C preform.…”
Section: Introductionmentioning
confidence: 99%